Foot and ankle biomechanics - L. J. Hunter; J. Fortune (AOSIS, 2000)
Foot and ankle injuries are common in sportsmen and the general population. The impact that the functional anatomy and biomechanics of the foot and ankle complex has on normal gait is reviewed. The abnormal biomechanics associated with overpronation and oversupination are discussed, as are their consequences. The management principles of foot and ankle injuries are briefly described.